Penulisan Abstrak Berbahasa Inggris untuk Karya Tulis Ilmiah - Mike Sari; Pretty Elisa Ayu Ningsih; Tri Saswandi; Rodiyal Ihsan (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2022)
In composing a scientific paper, unique is one of the foremost critical parts. Abstacrt is portion of logical paper that contained data around the paper itself. Theoretical is composed briefly, concisely, and conclusively. Be that as it may, STKIP Muhammadiyah Sungai Penuh understudies still faound challenges in composing a unique one. This movement pointed to socialize almost methods in composing an English theoretical for the logical composing to the understudies. the strategy utilized in this movement was socialization and address by the speaker who were the PkM group. This group was comprised of 4 English Think about Program speakers of STKIP Muhammadiyah Sungai Penuh. The result of this movement appeared that the understudies were able to (1) know what theoretical is (2) know the function of theoretical within the logical composing (3) utilize the fitting tenses in writing English theoretical. The victory of this action can be seen from the assessment did by the PkM group amid this movement handle and it might moreover be seen from the assessment did by the PkM group amid this movement handle, the process of oral test, questions and answer session, and it seem too be seen from the criticism given by the understudies at the conclusion of this action.